2019
DOI: 10.1016/j.ijdrr.2018.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Location reference identification from tweets during emergencies: A deep learning approach

Abstract: Twitter is recently being used during crises to communicate with officials and provide rescue and relief operation in real time. The geographical location information of the event, as well as users, are vitally important in such scenarios.The identification of geographic location is one of the challenging tasks as the location information fields, such as user location and place name of tweets are not reliable. The extraction of location information from tweet text is difficult as it contains a lot of non-stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 72 publications
(91 reference statements)
0
42
0
Order By: Relevance
“…11 But there is a significant difference in the social media usage pattern in terms of distance to the disaster site. 12,13 Citizens from affected areas turn to social media to share their experiences, seek help, and coordinate their response. Remote audiences participate in online interactions as spectators or volunteers who provide social support.…”
mentioning
confidence: 99%
“…11 But there is a significant difference in the social media usage pattern in terms of distance to the disaster site. 12,13 Citizens from affected areas turn to social media to share their experiences, seek help, and coordinate their response. Remote audiences participate in online interactions as spectators or volunteers who provide social support.…”
mentioning
confidence: 99%
“…Crisis informatics encompasses using social media in crisis management [33], [36]. The classification and evidence of social media intervention for crisis management includes social sensing [69], [70], which is further classified into mapping [71], [72], location identity [73]- [75] and geoweb [76]- [78]. Crowdsourcing [6], [55], [79]- [81] and digital volunteers [82]- [84] are the additional areas identified from the literature.…”
Section: Q2 What Is the Taxonomy Of Research Studies Conducted Inmentioning
confidence: 99%
“…However, crisis informatics is a multidisciplinary area of research, and various issues and challenges were reported from diverse literature and several of these challenges remain unanswered. [27], [75] reported the issue of dataset inaccessibility and inefficiency. This is important to link present research work with previous work [160]- [162].…”
Section: ) Open Issues and Challengesmentioning
confidence: 99%
“…Al-Olimat et al [1] proposed identifying the location names by traversing a tree of the tweet's n-grams to extract valid locations that exist in their pre-build region-specific gazetteer. Moreover, Hoang and Mothe [8] combined syntactic and semantic features to train traditional ML-based models whereas Kumar and Singh [13] trained a Convolutional Neural Network (CNN) model that learns the continuous representation of tweet text and then identifies the location mentions.…”
Section: Related Workmentioning
confidence: 99%